Topological Tail Pressure for Asymptotically Sub-Additive Continuous Potentials (Communications in Mathematical Research, 2019)
We define the topological tail pressure and the conditional pressure forasymptotically sub-additive continuous potentials on topological dynamical systemsand obtain a variational principle for the topological tail pressure without any additionalassumptions.